Association between dietary intake of one-carbon metabolism nutrients and hyperglycemia in coal-burning fluorosis areas of Guizhou, China - Ding, Li; Yang, Qinglin; Sun, Zhongming; Liu, Lu; Meng, Zeyu; Zhao, Xun; Tao, Na; Liu, Jun (Frontiers in Nutrition, 2022)
Aims: The present study aimed to investigate the association of habitual dietary intake of one-carbon metabolism nutrients with hyperglycemia in a fluorosis area in China. Method In a cross-sectional study, we recruited 901 villagers, ages ranging from 18-75, in Guizhou Province. Dietary data and other covariate data were obtained through an interviewer-administered questionnaire. We collected venous blood samples from participants who had fasted for one night to obtain fasting blood glucose levels and we categorized dietary intake of betaine, total choline, methionine, folate, vitamins B6 and B12, and choline subclasses into quartiles (Q1-Q4). The lowest quartile (Q1) served as the reference group. An unconditional logistic regression model was used to evaluate the protective effects of a dietary intake of one-carbon nutrients against hyperglycemia. We calculated Odds Ratios (ORs) with 95% confidence intervals (CIs). A presence or absence of fluorosis subgroup analysis was performed to determine the potential effect of fluorosis on hyperglycemia. Result After adjusting for potential confounding factors, we found that a greater intake of dietary vitamin B6, total choline and methyl-donor index was inversely associated with the occurrence of hyperglycemia (P-trend<0.05). However, there were no significant associations between hyperglycemia and the dietary intake of folate, vitamin B12, methionine, and betaine. As for the choline subgroups, it showed that the dietary intake of free choline, phosphatidylcholine, and glycerol phosphatidylcholine was negatively correlated with the occurrence of hyperglycemia (P<0.05). In contrast, there was no statistical association between dietary phosphatidylcholine and sphingomyelin and hyperglycemia (all P>0.05). The results of subgroup analysis showed that dietary intake of folate, vitamin B6, total choline, free choline, glycerol phosphorylcholine, and phosphocholine had a protective effect against the occurrence of hyperglycemia in the non-fluorosis subgroup, although no effects were observed in the fluorosis subgroup. There were significant interactions between these nutrients and fluorosis (P=0.010-0.048). Conclusion The study demonstrated that higher dietary intake of vitamin B6, total choline, methyl-donor index, free choline, glycerol phosphorylcholine, and phosphocholine in choline compounds were associated with a lower incidence of hyperglycemia. Moreover, the associations were modified by the presence or absence of fluorosis.